Factors Affecting the Quality of Online Learning During COVID-19: Evidence From a Developing Economy - Saleem, Farida; AlNasrallah, Wafa; Malik, Muhammad Imran; Rehman, Shafiq Ur (Frontiers in Education, 2022)
This descriptive study was conducted to evaluate the factors affecting the quality of online learning of Pakistani students during the Covid-19 pandemic. Developing economies such as Pakistan present a unique context to online education as there is limited access to technology, ITC services, and the internet for the general public. This paper integrates the factors affecting the online learning process of students while taking the situational factors as a boundary condition (moderating variable). Data were collected through a questionnaire administered to students studying in different universities in Pakistan. Stepwise linear regression and PROCESS Macro by Hayes (2013) was used for data analysis. Results revealed that university support, instructors’ support, and motivational factors predicted the quality of online learning. The situational factors negatively influenced the relationship of instructors’ support and motivational factors and the quality of online learning. University support and the quality of online learning relationships were not moderated by situational factors.